PERLINDUNGAN HUKUM DALAM TRANSAKSI NONTUNAI BERBASIS QUICK RESPONSE CODE INDONESIAN STANDARDS (QRIS) BERDASARKAN PERSPEKTIF HUKUM PERBANKAN - Adelia Dara Sasra; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Quick Response Indonesian Standard (QRIS) is the national standard for QR-Code-based payments, and it has been enforced by Bank Indonesia and ASPI beginning January 1, 2020. The industrial era 4.0 has brought about a considerable revolution in the payment system through the adoption of digital technologies. In order to facilitate the digitalization of payment systems and financial inclusion, particularly for Indonesia's MSME sector, this study intends to investigate legal protection in QRIS digital payment transactions. The UNGGUL concept (Universal, Easy, Profitable, and Direct) is used by QRIS to integrate different kinds of QR codes into a single system that makes non-cash transactions easier across a range of industries. But as society grows more reliant on digital payment methods, new legal issues and hazards arise that need for explicit consumer protection, data security, and service provider accountability. In order to provide a doctrinal perspective and implementation practices of regulations related to consumer protection in QRIS transactions, which require a strong legal basis and adequate protection mechanisms to ensure security and legal certainty for users, this study employs a normative legal method with a conceptual approach to analyze pertinent secondary legal materials, including government regulations, Bank Indonesia and OJK documents, and banking law literature.